Evaluation of sterilization possibility in water environment of activated nano MnO 2 coated on calcined laterite - Cao, Việt (Trường Đại học Khoa học Tự nhiên, 2016)
The TEM images of solution clearly reveal the presence of a large quantity of nanomanganese dioxide particles with lozenge shape and barked sphere with diameters around 30nm. The SEM images of material’s surface shows the distribution of barked sphere shape nano MnO2all over laterite surface. - Investigation sterilizing possibilities in static condition and dynamic condition. - Manganese has affect in sterilizing capabilities of BRM. It reacts with MnO2 to create semi-product [MnO2.Mn].nO2 which plays as strong sterilization substances.